Psychological and occupational impact of the COVID-19 pandemic on UK surgeons: a qualitative investigation - Judith Johnson; Tmam Abdulaziz Al-Ghunaim; Chandra Shekhar Biyani; Daryl O’Connor (BMJ Open)
Background The COVID-19 pandemic represents the greatest biopsychosocial emergency the world has faced for a century. The pandemic has changed how individuals live and work, and in particular, frontline healthcare professionals have been exposed to alarming levels of stress.Objective The aim of this study was to understand the professional and personal effects of COVID-19 pandemic on surgeons working in the UK National Health Service (NHS).Setting Surgical departments in the NHS.Design Between May and July 2020, as part of an ongoing study, we asked surgeons two open-ended questions: ‘What challenges are the COVID-19 crisis currently presenting to you in your work and home life?’ and ‘How is this stress affecting you personally?’ Thematic analysis was used for the qualitative data. Responses to the second question were also categorised into four groups reflecting valence: positive, neutral, mildly negative and strongly negative.Results A total of 141 surgeons responded to the survey and the results indicated that 85.8% reported that they were generally negatively affected by the COVID-19 pandemic, of which 7.8% were strongly affected in a negative way. Qualitative thematic analysis identified four key themes from responses relating to the impact of the pandemic: (1) changing and challenging work environment as a result of COVID-19; (2) challenges to professional life and development; (3) management of change and loss in the respondents’ personal lives; (4) emotional and psychological impacts.Conclusion The results highlighted the substantial emotional and psychological effects of the COVID-19 pandemic on surgeons’ mental health, particularly in relation to fear and anxiety, loss of motivation, low mood, stress and burnout. There is an urgent need for workplace support and mental health interventions to help surgeons cope with the difficulties they face during the ongoing COVID-19 pandemic.